FROM LYRICS TO EMPATHY: MEASURING EMOTIONAL VALUES AND EDUCATIONAL IMPLICATIONS OF JUSTIN BIEBER'S LONELY - Karisma Erikson Tarigan (Yayasan Education and Social Center, 2026)
This study examines how university students interpret the emotional qualities in Justin Bieber's 2020 song “Lonely” and explores how linguistic and musical components influence recommendation intentions and sympathetic reactions. The study used a mixed-methods approach, combining qualitative language analysis of the song's lyrics with quantitative survey data from 35 Indonesian university students. Eleven emotional and perceptual factors, such as grief, empathy, inspiration, authenticity, perspective change, lyrics-music effectiveness, melody contribution, and propensity to suggest, were measured on a 5-point Likert scale by participants in an online survey. According to the results, 71.4% of students rated authenticity as a 4 or 5, making it the most strongly perceived emotional value (M = 4.03, SD = 0.92). This was followed by inspiration (M = 3.49, SD = 1.15), melancholy (M = 3.37, SD = 1.06), and empathy (M = 3.34, SD = 1.14). Correlation analysis showed strong positive correlations between authenticity and empathy (r = 0.58), melancholy and empathy (r = 0.61), empathy and viewpoint change (r = 0.53), and lyrics-music effectiveness and recommendation likelihood (r = 0.55). 65.7% of students rated the likelihood of recommending as 4 or 5, with a mean score of 4.00 (SD = 1.08). These results show that “Lonely” is a linguistically rich emotional text that uses authenticity as the primary motivator of empathic involvement, converting feelings of loneliness into shared empathy. With practical implications for music education, music therapy, songwriting, and the music industry, the study makes an empirical contribution to affective linguistics and music psychology by offering a repeatable methodology for assessing emotional reactions to pop songs.